Comportamento espacial do desempenho tributário dos municípios de Minas Gerais - Leonel, Henrique Silveira (2022)
The main objective of the dependence study was to evaluate the spatiality of tax performance among the municipalities in the state of Minas Gerais. This research is based on Spillover Effect and Yardstick Competition theories. A final sample consisted of 739 municipalities, which is equivalent to 86.64% of the population, during the period from 2013 to 2020. The following variables were used to carry out the study: IFGF-Geral, IFGF-Autonomia, IFGF-Liquidez, IFGF – Gastos com pessoal and IFGF-Investimentos available on the FIRJAN website. By the clustering method, the findings appear similar to those of municipalities that resemble similar among those similar to others. In the method, all characteristics such as moderate or strong degree of spatial dependence, or all similar characteristics can infer that the municipalities are geographically similar, but can infer that the rest of the locations. However, as much as the IFGF-Personnel spending has a spatial presentation, it still showed great spatial disparity between nearby municipalities, this may be due to the characteristics of individuals in the municipalities of Minas Gerais. In general, as a contribution to the literature, it was possible to identify the existence of Spillover Effect or Yardstick Competition among the municipalities of the state of Minas Gerais, as well as a new methodology applied to the Accounting Sciences course, geostatistics.